PENGARUH PENGELUARAN PEMERINTAH, PENDIDIKAN, DAN UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA PADA PROVINSI DI INDONESIA - Soraya Amelia; Syamsul Amar; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study purpose to analyze the effect of government expenditure, education, and wages on labor productivity in provinces in Indonesia. This type of research is descriptive research, the data used are secondary data analyzed by panel data regression can be estimated using three models, namely Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). To get the best model, two tests were used, namely the Chow test and the Hausmann test. In this study, the best model is the Fixed Effect Model. The research findings show that government expenditure, education and wages have a positive and significant effect on labor productivity in the province in Indonesia.And government spending, education, and wages togheter have a positive and significant effect on labor productivity in the province in Indonesia.